Aportes de investigación. El caso de un estudio clínico controlado. Reflexiones teórico - metodológicas (1998)
ABSTRACT: This article shows the theoretical and methodological aspects, which allowed the design of an experiment on the transformation of a food into a drug. The purpose was to give the community an oral rehydration solution, using a home-made food (plantain farine) as a raw material, taking into consideration that not all communities have access to oral rehydration salts. This alternative would contribute to reduce mortality due to diarrhoea, which is still highly prevalent in some zones of Colombia as well as other developing countries. This new proposal is closer to the food habits of the population, because plantain is a everyday food in the Atlantic litoral zones as well in the province of El Valle del Cauca, and the coffee producing region among others. For instance, in the Emberá, indigenous community, plantain is the base its food security and it is a usual food during all the year. Futhermore, this study takes and validates popularly knowledge when searching traditional elements in the community to be put under rigorous analysis and methodology in order to prove its use and efficacy. Finally, this article shows the theoretical, methodological and ethical aspects, which give directions for the searching, as in this case, for the dehydration due to diarrhoea. The results of this research were published in Acta Paediatrica (1997; 86:1051), and they may be used in other regions of the tropic zone where platain is produced e.g Central America and Africa.